1998
DOI: 10.1159/000007982
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler Monitoring of Intracranial Pressure Therapy with Mannitol, Sorbitol and Glycerol in Patients with Acute Stroke

Abstract: Introduction: The noninvasive management of the conservative therapy for intracranial pressure (ICP) with hyperosmolar substances is a central problem in the treatment of brain edema. Using transcranial Doppler (TCD), a continuous monitoring of ICP is now possible, because the TCD pulsatility index (PI) intraindividually closely correlates with the level of ICP. Patients and Methods: We administered an ICP-lowering treatment 113 times in 10 patients with intracranial bleeding or ischemic stroke who also had si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…20 Interestingly, in the present study, higher pretreatment SBP values were observed in patients with persisting high-resistance occlusions. Because brain swelling is associated with increased resistance to residual blood flow, 21,22 it may be assumed that high pretreatment blood pressure values by exacerbating early brain swelling could have a possible detrimental effect on vessel recanalization. In addition, cyto- toxic edema can impede microcirculation in the core of infarction during the first 3 hours of ictus as seen in animal models of the MCA occlusion.…”
Section: Association Of Increased Pretreatment Systolic Blood Pressurmentioning
confidence: 99%
“…20 Interestingly, in the present study, higher pretreatment SBP values were observed in patients with persisting high-resistance occlusions. Because brain swelling is associated with increased resistance to residual blood flow, 21,22 it may be assumed that high pretreatment blood pressure values by exacerbating early brain swelling could have a possible detrimental effect on vessel recanalization. In addition, cyto- toxic edema can impede microcirculation in the core of infarction during the first 3 hours of ictus as seen in animal models of the MCA occlusion.…”
Section: Association Of Increased Pretreatment Systolic Blood Pressurmentioning
confidence: 99%
“…29,61,62 Other descriptions include effacement of the ipsilateral sulci and lateral ventricle 63 and CT signs of elevated ICP. 64 Most commonly, the degree of midline shift is used as the benchmark for radiographic deterioration, either undefined 16,60,65 or specified as >5 mm at the level of septum pellucidum, 19,41,47,[66][67][68] >2 mm at the level of septum pellucidum or pineal gland, 69,70 or >10 mm. 71 Although all these arbitrary parameters are indicative of tissue shift, further development and validation of serial CT measures that identify patients at highest risk of clinical deterioration are required.…”
Section: Ct Imagingmentioning
confidence: 99%
“…The reason for poor outcome after initial high blood pressure seems more complex. High blood pressure after acute ischemic stroke causes brain edema [10], and brain edema decreases cerebral blood flow [11, 12], thus aggravating cerebral ischemia. Another mechanism could be that endogenous tPA release is reduced when blood pressure is high due to the damage at the endothelium [13–15].…”
Section: Initial Blood Pressure and Outcomementioning
confidence: 99%